2006
DOI: 10.1007/s10278-005-7667-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Queries Using Structured Query Language (SQL) to Determine the Utilization of Comparison Imaging in Radiology Reports Stored on PACS

Abstract: The purpose of this research was to develop queries that quantify the utilization of comparison imaging in free-text radiology reports. The queries searched for common phrases that indicate whether comparison imaging was utilized, not available, or not mentioned. The queries were iteratively refined and tested on random samples of 100 reports with human review as a reference standard until the precision and recall of the queries did not improve significantly between iterations. Then, query accuracy was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This category covers applications that identify quality indicators of radiologic practice (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). These indicators can be used for internal quality assurance, comparison to established guidelines, or fulfilling legal requirements.…”
Section: Quality Assessment Of Radiologic Practicementioning
confidence: 99%
See 2 more Smart Citations
“…This category covers applications that identify quality indicators of radiologic practice (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). These indicators can be used for internal quality assurance, comparison to established guidelines, or fulfilling legal requirements.…”
Section: Quality Assessment Of Radiologic Practicementioning
confidence: 99%
“…A subgroup of studies in this category exploited NLP to assess quality of content and format of the radiology report itself (64)(65)(66)(67)(68). Good radiologic practice is subject to conventions for standardized reporting.…”
Section: Clinical Support Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work complements prior work that has shown that NLP algorithms can be used to ascertain aspirin exposure from free-text progress notes,4,17 but may have the advantage of being more easily implemented because many health systems may have programmers familiar with SQL, whereas NLP requires more advanced training. Our work also expands prior work implementing SQL-based search of free-text notes for exposure and outcome ascertainment 26,27. We utilize not only inherent features to the SQL language, but supplement our methods with structured data to create a stronger algorithm.…”
Section: Discussionmentioning
confidence: 98%
“…However, we were previously successful in mining data directly from free-text radiology reports using simple rule-based queries based on standard languages 12. Other authors have similarly used regular expressions for improving information retrieval 13.…”
Section: Introductionmentioning
confidence: 99%